2014
DOI: 10.4067/s0717-65382014000200002
|View full text |Cite
|
Sign up to set email alerts
|

Reach scale ecologic influence of in-stream large wood in a Coastal Mountain range channel, Southern Chile

Abstract: 60%) among LW-low-volume reaches. Results confirm the hypothesis that OM retention and benthic macro-invertebrate diversity and abundance were higher in high LW volume reaches. The higher diversity and abundance of macro-invertebrates associated with LW accumulations confirm that logjams constitute a biotope that offers shelter and food. These results can guide the assessment of environmental impacts of stream intervention and restoration projects. The study was undertaken within the framework of Project Fonde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…More abundant research has developed since 2007 focusing mainly on LW morphologic and hydraulic roles (Andreoli et al, 2007;Comiti et al, 2008;Mao et al, 2008Mao et al, , 2013Cadol et al, 2009;Wohl et al, 2009Wohl et al, , 2012Cadol and Wohl, 2010;Iroumé at al., 2010Iroumé at al., , 2011Iroumé at al., , 2014Ulloa et al, 2011) and also on the ecology of low-order mountain channels (Vera et al, 2014). First analyses of LW mobilization in Latin American streams are the reports by Andreoli et al (2008), Mao et al (2008), andIroumé et al (2011).…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 2 more Smart Citations
“…More abundant research has developed since 2007 focusing mainly on LW morphologic and hydraulic roles (Andreoli et al, 2007;Comiti et al, 2008;Mao et al, 2008Mao et al, , 2013Cadol et al, 2009;Wohl et al, 2009Wohl et al, , 2012Cadol and Wohl, 2010;Iroumé at al., 2010Iroumé at al., , 2011Iroumé at al., , 2014Ulloa et al, 2011) and also on the ecology of low-order mountain channels (Vera et al, 2014). First analyses of LW mobilization in Latin American streams are the reports by Andreoli et al (2008), Mao et al (2008), andIroumé et al (2011).…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…In Vuelta de Zorra reaches 6 to 9, and especially reach 8, experienced most of the movement during the study period. These reaches feature an average LW volume of 243 m 3 /ha of bankfull channel, while the average LW volume in the segment is 109 m 3 /ha (Iroumé et al, 2014), have between 2 and 5 logjams, while all the other reaches have ≤ 2 logjams, and on average, stream channel in these reaches is wider (at bankfull level) and less steep than mean segment bankfull width and longitudinal slope (Ruz, 2013). In the Tres Arroyos, LW movement is concentrated mainly in reaches 8 to 10 with an average stock of 1288 m 3 /ha of LW, while the mean segment LW volume is 1057 m 3 /ha (Iroumé et…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 1 more Smart Citation
“…Logs, especially if jammed, can create steps (Rosenfeld and Huato, ), increase flow resistance (Cadol and Wohl, ), store organic matter (Beckman and Wohl, ; Tank et al ., ), and increase the connectivity with floodplains (Sear et al ., ). It has also been demonstrated that in‐channel wood increases habitats and biological diversity (Cordova et al ., ; Gerhard and Reich, ; Vera et al ., ), principally by augmenting morphological diversity and complexity (Gurnell et al ., ). Indeed, the presence of LW can increases fish number and biomass (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…KEYWORDS channel morphology, displacement length, large wood dynamics, mountain streams 1 | INTRODUCTION Understanding large wood (hereafter referred to as LW, i.e., wood pieces at least 1 m in length and at least 10 cm in diameter) dynamics in rivers is critical for many disciplines including those addressing flood hazard and risk assessments. Moreover, the geomorphic (Beechie & Sibley, 1997;Chen, Wei, Scherer, & Hogan, 2008;Robison & Beschta, 1990) and ecological (Chen et al, 2008;Diez, Elosegi, & Pozo, 2001; Vera, Jara, Iroumé, Ulloa, & Barrientos, 2014) significance of LW on stream ecosystems is widely recognized. LW is a key component of river systems, and although LW removal from stream channels has been a very common management strategy during past centuries (Wohl, 2014), this paradigm is now changing in such a way that wood is often reintroduced to watercourses as a river restoration technique (Buxton, 2010;Kail, 2003;Roni, Beechie, Pess, & Hanson, 2015).…”
mentioning
confidence: 99%